2016
DOI: 10.15405/epsbs.2016.11.02.43
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Work Ethics and Job Performance

Abstract: Work ethics are normally associated with the way employees do their work which may be perceived as ethical or unethical. This study discusses the relationship between work ethics and job performance. A structural model was constructed to test the effects of work ethics on job performance. 157 respondents from randomly selected SMEs involved in retail trade textile service located in Selangor, Kuala Lumpur and Johor were given self-administered questionnaires using a six-point Likert response scale. Multidimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Other researchers have concluded in similar results that organizational learning has a significant relationship with human resource productivity (18)(19). Another study showed that work ethic leads to improved organizational performance environment of employees (20). Other results showed that work ethic is related to productivity and quality of life of employees (21).…”
Section: Introductionmentioning
confidence: 98%
“…Other researchers have concluded in similar results that organizational learning has a significant relationship with human resource productivity (18)(19). Another study showed that work ethic leads to improved organizational performance environment of employees (20). Other results showed that work ethic is related to productivity and quality of life of employees (21).…”
Section: Introductionmentioning
confidence: 98%
“…Pemimpin yang paling sukses memiliki integritas, mereka menginspirasi orang dengan visi bersama tentang masa depan, mereka menetapkan tujuan yang jelas dan memotivasi orang ke arahnya, mereka mengelola pengiriman, dan mereka berkomunikasi dengan baik dengan tim. Salahudin et al, (2016) Etika adalah salah satu masalah paling kritis dalam bisnis dan khususnya dalam manajemen sumber daya manusia. Budaya etika yang baik dalam suatu organisasi akan memberikan arahan dan bimbingan dalam berbagai bidang guna membangun karyawan yang bersatu, harmonis dan beretika.…”
Section: Pendahuluanunclassified
“…Dalam penelitian menurut Shahrul Nizam bin Salahudina, Mohd Nur Ruzainy bin Alwia, Siti Sarah binti Baharuddina & Siti Syafina binti Halimata (2016) tentang The Relationship between Work Ethics and job Performance. menyatakan bahwa ada hubungan yang signifikan antara etos kerja dan kinerja.…”
Section: Kaitan Etika Kerja Dengan Kinerja Karyawanunclassified